101 challenges in C programming - Kanetkar, Yashavant; Kanetkar, Yashavant; Kanetkar, Aditya (New Delhi BPB Publisher, 2017)
About the Book: 101 Challenges in C Programming Often one thinks that one knows C programming and moves on to learning languages like C++, Java or Python. That is perhaps a mistake. Unless you have a through grinding and sufficient exposure to all features of C programming, you are likely to find yourself an incomplete programmer. To address this precise issue Yashavant and Aditya have crafted well thought out 101C Programming Challenges their complete solution sample runs and explanation. These Challenges would test and improve your knowledge in every aspect of C Programming. Contents: Chapter 1: Basic Control Flow challenges Chapter 2: Decision Making challenges Chapter 3: Looping
Keywords: Array Challenges; Function challenges; Looping challenges; Statistics